PENGARUH RASIO UMPAN, VARIASI JENIS SAMPAH ORGANIK, DAN KUALITAS KOMPOS HASIL BIOKONVERSI MENGGUNAKAN LARVA BLACK SOLDIER FLY (Hermetia Illucens) - Haryandi, Haryandi; Izzy, Syauqy Nur (Universitas Muhammadiyah Mataram, 2020)
One technology that can degrade organic waste is bioconversion using Black Soldier Fly (BSF) or Hermenetia illucens which content high protein source. This research studied the effect of BSF production withg varying feed rate, type of waste, and the quality of compost that produced compare with the Indonesia government requirement. The experiment was conducted at PT. Biomagg Sinergi Internasional, an organic waste processing company in West Java. The results of this study indicated the highest BSF biomass value in the treatment of catering with feed rate of 200 mg/larvae/ day, the highest substrate consumption value was on fermentation waste with feed rate 100 mg/ larvae /day is 72.05%, the highest survival rate was the catering waste with feed rate of 100mg/larvae / day, and the highest value of waste reduction index was the fermentation waste with 100 mg / larvae / day feed rate is 4.80%. The quality of compost produced by bioconversion conducted by PT. BSI has met the quality standards of organic fertilizers based on Permentan No. 70 / Permentan / SR.140 / 10/2011 concerning organic fertilizer.Â